Chemical composition and biological activities of the essential oil from Pulicaria undulata (L.) C. A. Mey. growing wild in Egypt. Issue 16 (17th August 2020) - Mustafa, Ahmed M.; Eldahmy, Samih I.; Caprioli, Giovanni; Bramucci, Massimo; Quassinti, Luana; Lupidi, Giulio; Beghelli, Daniela; Vittori, Sauro; Maggi, Filippo
Abstract: Pulicaria undulata is used as a traditional herbal remedy in Egypt. We used gas chromatography-mass spectrometry for analysis of essential oil of this plant growing wild in Egypt and 64 compounds were identified. The oil was rich in oxygenated monoterpenes (64.0%) and aromatic derivatives (18.8%). The major components were carvacrol (46.5%), xanthoxylin (18.1%) and carvotanacetone (8.7%). The oil of the Egyptian plant showed significant differences from the oil results reported on this species derived from different accessions. Antioxidant activity was performed by FRAP, DPPH and ABTS assays, and the oil demonstrated a powerful antioxidant properties. Furthermore, cytotoxicity was assessed using MTT assay against three cell lines (A375, T98G, HCT116) and the oil showed moderate results with IC50 of 18.53, 40.64 and 22.23 μg/ml; respectively. The oil showed a good anti-acetylcholinesterase activity (IC50 = 139.2 μg/ml) using Ellman method. In conclusion, the studied oil exhibited a peculiar fingerprint and promising biological activities. Graphical Abstract: